Associations of Physical Activity and Sedentary Behaviors with Dietary Behaviors among US High School Students - Kann, Laura; Demissie, Zewditu; Michael, Shannon; Lowry, Richard; Galuska, Deborah A. (Journal of Obesity, 2015)
Background. Physical activity (PA), sedentary behaviors, and dietary behaviors are each associated with overweight and obesity among youth. However, the associations of PA and sedentary behaviors with dietary behaviors are complex and not well understood. Purpose. To describe the associations of PA and sedentary behaviors with dietary behaviors among a representative sample of US high school students. Methods. We analyzed data from the 2010 National Youth Physical Activity and Nutrition Study (NYPANS). Using logistic regression models which controlled for sex, race/ethnicity, grade, body weight status, and weight management goals, we compared dietary behaviors among students who did and did not meet national recommendations for PA and sedentary behaviors. Results. Students who participated in recommended levels of daily PA (DPA) and muscle strengthening PA (MSPA) were more likely than those who did not to eat fruits and vegetables. Students who exceeded recommended limits for television (TV) and computer/video game (C/VG) screen time were less likely than those who did not to consume fruits and vegetables and were more likely to consume fast food and sugar-sweetened beverages. Conclusions. Researchers may want to address PA, sedentary behaviors, and dietary behaviors jointly when developing health promotion and obesity prevention programs for youth.